A framework for understanding pastoralist-led strategies to secure land and resource access: Case studies from Kenya - Lind, Jeremy; Flintan, Fiona E. (Springer, 2025)
This paper examines pastoralist-led strategies to secure access to land and resources in contexts of limited tenure security. Efforts to secure land access for pastoralists through statutory frameworks often fall short, necessitating a rethinking of approaches to support marginalized and less vocal groups. This article presents a framework for systematically analyzing pastoralist strategies, with four guiding elements: contextual drivers of land pressure, agency and networks that stakeholders mobilize, the characteristics of specific strategies, and their impacts.